2006
DOI: 10.3171/jns.2006.104.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Seizure and memory outcome following temporal lobe surgery: selective compared with nonselective approaches for hippocampal sclerosis

Abstract: Both ATL and SA can lead to similar favorable seizure control in patients with MTLE/HS. Preliminary data suggest that postoperative verbal memory scores may improve in patients who undergo selective resection of a sclerotic hippocampus in the dominant temporal lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 42 publications
6
110
0
1
Order By: Relevance
“…Nevertheless, many other studies claim that SelAH confers lower cognitive morbidity, mostly involving language and verbal memory. In fact, many of these studies agree that ATL is particularly cognitively harmful when performed on the dominant hemisphere 6,7,23,27,28,29 -an observation that was also noted in our series.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Nevertheless, many other studies claim that SelAH confers lower cognitive morbidity, mostly involving language and verbal memory. In fact, many of these studies agree that ATL is particularly cognitively harmful when performed on the dominant hemisphere 6,7,23,27,28,29 -an observation that was also noted in our series.…”
Section: Discussionsupporting
confidence: 69%
“…It has been described by most major series that postoperative seizure control does not differ significantly between the two approaches 7,13,14,15,16,17,18,19,20,21 . Nonetheless, three studies have found better seizure-control in patients submitted to ATL 4,22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the surgical approach has not been found to be predictive of outcome. 9,36,46 The incidence of failure was 8.9% (61/686; Table 1). Hardy et al 16 and Hennessy et al 17 did not use the Engel classification but documented a failure rate (similar to Engel Class III/IV) of 7.6% and 12%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recurrent seizures might also result in deterioration of both verbal and spatial memory functions over time. Some reports show improvement in both verbal and spatial memory functions following SAH (1,24). Despite the risk of morbidity and mortality of surgery, epileptic seizures themselves have a higher risk, and surgical treatment has favorable and costeffective results in comparison with AEDs (25).…”
Section: Discussionmentioning
confidence: 99%